Consensus and Security Control of Multi-agent Systems Based on Set-membership Estimation with Time-varying Topology under Deception Attacks - Zhu, Yanfei; Liu, Hang; Li, Chuanjiang; Yu, Jiahao (International journal of control, automation, and systems, 2022)
This paper is concerned with the consensus and security of leader-follower multi-agent systems with time-varying topology, where each follower’s sensor-to-controller channel and controller-to-actuator channel are subject to unknown but bounded (UBB) random deception attacks. A novel set-membership estimation and control framework is presented to realize system consensus, input-to-state stability and security performance, in which each controller receives arbitrary estimates from itself and neighbor set-membership estimators. Based on the Lyapunov functional and stochastic control method, a sufficient condition on the existence of estimators and controllers is derived. Then, a convex optimization algorithm is established to deal with the proposed framework. Finally, the effectiveness of the method is verified by numerical simulation.